Physical activity and diet for Type 2 Diabetes reduction among older people living with HIV in Harare - Nongiwe L. Mhlanga; Thinavhuyo R. Netangaheni (Health SA Gesondheid: Journal of Interdisciplinary Health Sciences, 2024)
Background: People living with HIV (PLWH) are ageing, and face increased risk for developing Type 2 Diabetes. Physical activity and diet are effective in reducing Type 2 Diabetes risk. However, there is variation in how older PLWH engage in physical activity and healthy eating.